2022
DOI: 10.1111/appy.12520
|View full text |Cite
|
Sign up to set email alerts
|

Low mental health literacy and its association with depression, anxiety and poor sleep quality in Chinese elderly

Abstract: Background Mental health literacy (MHL) is rarely reported in the Chinese elderly. This study explored the pattern of MHL in the Chinese elderly in relation to depression, anxiety and poor sleep quality. Methods A cross‐sectional study was conducted among older adults in Guangzhou, south China. Participants were investigated face‐to‐face using the Chinese National Mental Health Literacy Scale, the Patient Health Questionnaire‐9 item (PHQ‐9), the 7‐item Generalized Anxiety Disorder (GAD‐7) and the Pittsburgh Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
1
10
1
Order By: Relevance
“…In China, anxiety disorders were the most common class of disorders, with the lifetime prevalence of 7.6% ( 8 ). A cross-sectional study conducted among older adults in south China reported the prevalence of anxiety as 7.9% ( 9 ). A survey included 4,103 community-dwellings adults aged 60 and older from the West China showed that anxiety were prevalent in 20.8% of all participants ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, anxiety disorders were the most common class of disorders, with the lifetime prevalence of 7.6% ( 8 ). A cross-sectional study conducted among older adults in south China reported the prevalence of anxiety as 7.9% ( 9 ). A survey included 4,103 community-dwellings adults aged 60 and older from the West China showed that anxiety were prevalent in 20.8% of all participants ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing studies about anxiety among Chinese are based on specific populations [such as children and adolescents ( 21 ), some occupational groups ( 22 ), or patients with certain diseases ( 23 )], medium sample size ( 10 ) (less than 10,000 respondents) and limited sample area ( 9 ) (studies are usually conducted in several cities or regions). The research method tends to be traditional logistic regression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that participants who experienced a heavier economic loss during the COVID-19 wave were more likely to suffer from depressive symptoms, which is consistent with previous findings ( Hertz-Palmor et al, 2020 ; Argabright et al, 2022 ). People who were economically disadvantaged were more likely to experience financial insecurity, unhealthy lifestyles, poor living conditions, and reduced social capital ( Lund and Cois, 2018 ; Jin et al, 2020 ; Ding et al, 2022 ). All these factors might lead to a higher risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…112 For seniors, low mental HL was associated with depression, anxiety, and poor sleep quality. 113 Diseases-specific HL. Eleven studies were identified that accessed disease-specific HL of participants, including three in diabetes HL, three in infectious disease-specific HL, two studies in dementia literacy, one in high blood pressure HL, one in postpartum depression literacy, and one in melanomarelated HL.…”
Section: Main Outcomes Of Hl Studies In Asiamentioning
confidence: 99%